Europe's emerging economic and monetary union. - Frenkel, Jacob A. (1991)
Looks at key issues relating to the design and implementation of monetary policy in the emerging EMU. Focuses on the interrelationships among price stability, current account equilibrium, and exchange rate stability. Considers the implications of fiscal policy for the conduct of monetary policy, along with alternative ways of encouraging fiscal discipline.